2010
DOI: 10.1063/1.3298647
|View full text |Cite
|
Sign up to set email alerts
|

Minimum-error state discrimination constrained by the no-signaling principle

Abstract: We provide a bound on the minimum error when discriminating among quantum states, using the no-signaling principle. The bound is general in that it depends on neither dimensions nor specific structures of given quantum states to be discriminated among. We show that the bound is tight for the minimum-error state discrimination between symmetric (both pure and mixed) qubit states. Moreover, the bound can be applied to a set of quantum states for which the minimum-error state discrimination is not known yet. Fina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…We first solved the problem for an even number of symmetric qubits with use of the no-signaling principle. Here both methods used for QSD [8][9][10][11] and QSE [12] are combined to get the solutions. We showed that, with use of the no-signaling principle, conditional probability always has the form α cos 2 (φ/2) + β.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We first solved the problem for an even number of symmetric qubits with use of the no-signaling principle. Here both methods used for QSD [8][9][10][11] and QSE [12] are combined to get the solutions. We showed that, with use of the no-signaling principle, conditional probability always has the form α cos 2 (φ/2) + β.…”
Section: Discussionmentioning
confidence: 99%
“…(16). The bound reduces to P guess ≤ 1/(N p) when p i ≡ p [10]. The p in our case is calculated as p = 1/(1 + | r|| sin θ|) [10].…”
Section: Main Contentsmentioning
confidence: 99%
See 3 more Smart Citations